2020
DOI: 10.1016/j.isci.2020.101516
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Proteome Changes in the Myocardium of a Pig Model for Duchenne Muscular Dystrophy

Abstract: Duchenne muscular dystrophy (DMD), caused by mutations in the dystrophin gene, is characterized by progressive muscle weakness. Even though DMD manifests first in skeletal muscle, heart failure is a major cause of death in late-stage DMD. To get insights into DMD-associated cardiomyopathy, we performed a proteome analysis of myocardium from a genetically engineered porcine DMD model resembling clinical and pathological hallmarks of human DMD. To capture DMD progression, samples from 2-day-and 3-month-old anima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 51 publications
3
12
0
Order By: Relevance
“…Overall, in skeletal muscle and myocardium differentially expressed proteins and associated biological processes and pathways largely overlap with previous observations made in cloned DMD Y/pigs (21,22).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Overall, in skeletal muscle and myocardium differentially expressed proteins and associated biological processes and pathways largely overlap with previous observations made in cloned DMD Y/pigs (21,22).…”
Section: Discussionsupporting
confidence: 80%
“…Our initial model was based on DMD exon 52 deficient male cells, which were used to generate DMD Y/pigs by SCNT (10). Although the model showed the clinical phenotype and provided new insights into the molecular DMD pathology in skeletal muscle (21) and heart (22), the affected animals died before sexual maturity and could only be propagated by cloning. Epigenetic abnormalities associated with this biotechnology may per se affect the phenotype of the offspring, which was evident by a highly variable birth weight (10).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, all piglets obtained after SCNT were dystrophin deficient and showed clinical, biochemical, and pathological hallmarks of human DMD, but developed them in an accelerated mode [ 36 ]. A potential explanation for the highly progressive DMD pathology in pigs, which is associated with characteristic changes of the proteome profiles of skeletal muscle [ 37 ] and myocardium [ 38 ], is their rapid muscle growth by muscle cell hypertrophy and the associated mechanical strain on the sarcolemma. Since the cloned DMD piglets died before sexual maturity with a maximum life expectancy of 3–4 months, the model could not be propagated by breeding.…”
Section: Animal Experiments For Dmd Gene Editing Therapy: Proof Of Principle and Challengesmentioning
confidence: 99%
“…Since mdx mice do not completely recapitulate DMD, particularly DAC, Tamiyakul et al performed a proteomic study on the porcine DMD model [64]. Using an isobaric tag for relative and absolute quantitation (iTRAQ) quadro plex-based proteomic approach coupled with OFFGEL pre-fractionation of peptides before MS analysis, they compared heart tissue from WT and DMD pigs at different ages (2-day-old representing an early pre-symptomatic stage and 3-month-old to account for a more advanced disease stage).…”
Section: Proteomic Investigations Of Dystrophin Deficiencymentioning
confidence: 99%
“…Furthermore, decreased levels of DGC components indicate sarcolemma destabilisation and impaired signal transduction. A direct comparison of the degree of proteome alterations in skeletal muscle and heart tissue indicated that DAC progression is not only slower compared to skeletal muscle but also characterised by different biological and biochemical alterations [64].…”
Section: Proteomic Investigations Of Dystrophin Deficiencymentioning
confidence: 99%